Characteristics of patients with atrial fibrillation prescribed antiplatelet monotherapy compared with those on anticoagulants: insights from the GARFIELD-AF registry. (20th December 2017) - Verheugt, Freek W A; Gao, Haiyan; Al Mahmeed, Wael; Ambrosio, Giuseppe; Angchaisuksiri, Pantep; Atar, Dan; Bassand, Jean-Pierre; Camm, A John; Cools, Frank; Eikelboom, John; Kayani, Gloria; Lim, Toon Wei; et al.
Abstract: Aims: Current atrial fibrillation (AF) guidelines discourage antiplatelet (AP) monotherapy as alternative to anticoagulants (ACs). Why AP only is still used is largely unknown. Methods and results: Factors associated with AP monotherapy prescription were analysed in GARFIELD-AF, a registry of patients with newly diagnosed (≤6 weeks) AF and ≥1 investigator-determined stroke risk factor. We analysed 51 270 patients from 35 countries enrolled into five sequential cohorts between 2010 and 2016. Overall, 20.7% of patients received AP monotherapy, 52.1% AC monotherapy, and 14.1% AP + AC. Most AP monotherapy (82.5%) and AC monotherapy (86.8%) patients were CHA2 DS2 -VASc ≥2. Compared with patients on AC monotherapy, AP monotherapy patients were frequently Chinese (vs. Caucasian, odds ratio 2.73) and more likely to have persistent AF (1.32), history of coronary artery disease (2.41) or other vascular disease (1.67), bleeding (2.11), or dementia (1.81). The odds for AP monotherapy increased with 5 years of age increments for patients ≥75 years (1.24) but decreased with age increments for patients 55–75 years (0.86). Antiplatelet monotherapy patients were less likely to have paroxysmal (0.67) or permanent AF (0.57), history of embolism (0.56), or alcohol use (0.90). With each cohort, AP monotherapy declined ( P <0.0001), especially non-indicated use. AP + AC and no antithrombotic therapy were unchanged. However, even in 2015 and 2016, about 50% of AP-treated patients had no indication except AF (71% were CHA2 DS2 -VASc ≥2). Conclusion: Prescribing AP monotherapy in newly diagnosed AF has declined, but even nowadays a substantial proportion of AP-treated patients with AF have no indication for AP. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT01090362.